Emerging Educational Technologies and Their Influence on Preschool Learning Outcomes - Annisa Ardien; Novena Ulita; Kamal Arif Al-Farouqi; Solahudin (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
This study examines the influence of emerging educational technologies on preschool learning outcomes amid the increasing integration of digital tools such as educational applications, interactive games, and multimedia based platforms in early childhood education. Using a quantitative approach with a quasi experimental design, the study involved 167 preschool students who participated in technology-enhanced learning activities over a defined instructional period. Data were collected through structured observations, standardized assessments of learning outcomes, and teacher evaluations to comprehensively measure cognitive, social, and emotional development. The findings indicate that the use of emerging educational technologies has a statistically significant positive effect on preschool learning outcomes, particularly in improving student engagement, foundational literacy skills, problem-solving abilities, and cooperative behaviors compared to traditional instructional methods. In addition, teachers reported better classroom interaction, increased instructional efficiency, improved student participation, and more effective learning management when digital tools were implemented appropriately. These results suggest that the integration of technology not only enhances academic related skills but also supports broader developmental aspects of young learners. Therefore, the study highlights the importance of thoughtful and well structured implementation of educational technologies to maximize their benefits in early childhood education settings, ensuring sustainable, inclusive, and developmentally appropriate learning experiences.